Coordinating multiactivity transitions in dance rehearsals: spatial configurations and instructional practices - Krug, Maximilian (Frontiers in Communication, 2025)
This study explores the mechanisms behind activity transitions in dance rehearsals, focusing on how participants manage multiactivities in instructional situations. The research uses multimodal conversation analysis to examine the spatial configurations and interactional practices of a professional choreographer and two nonprofessional dancers. The analysis reveals how participants create activity transitions, mobilize resources, and maintain continuity across activities, emphasizing the crucial role of spatial positioning and timing in managing transitions. By maintaining one activity while introducing others, participants effectively coordinate multiple activities without disrupting the rehearsal’s flow. The findings contribute to an understanding of multiactivity in social interactions and offer practical insights for instructional practices in dance and other embodied activities.